Energy Yield of the Carbonized Plant Leaf, Petiole and Branch Biomass Briquettes for Sustainable Production of Future Fuels - Nurhayati, Arry Y.; Naufal, Achmad Zulfi N.; Hariadi, Yuda C. (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2022)
The effective use of waste biomass is an important factor for sustainability and global energy consciousness. Unsurprisingly, tree wastes such as leaves, petiole and branch are plentiful during trimming or autumn season which offer an economical source of biomass. The objective of this study was to probe the mechanical and thermal characteristics of briquettes created from tree waste of langsat, guava and rambutan tree. Collected tree wastes (leaves, petiole and branches) were chopped, mixed and then carbonized at 400-600 °C using a Charcoal Retort tube system. The briquettes were molded manually using a Hydraulically Briquetting Machine at pressures of 20 and 50 N/cm2 for half an hour to 3 hours with regards on the type, density and fragments of the tree. Two system and machine were designed and fabricated by Biophysics Lab, Dept. of Physics, Faculty of Mathematics and Natural Sciences, Universitas Jember. Results indicated that briquettes made from tree waste of langsat, guava and rambutan have signs of mechanical and thermal properties which can be used as briquettes for various industrial uses.Keywords: Sustainability, Alternate fuel, Tree waste, Biomass, Briquette